ANA testing in the presence of acute and chronic infections. Issue 5 (2nd September 2016) - Litwin, Christine M.; Binder, Steven R.
ABSTRACT: Autoantibody testing is performed to help diagnose patients who have clinical symptoms suggestive of possible autoimmune diseases. Antinuclear antibodies (ANA) are present in many systemic autoimmune conditions such as systemic lupus erythematosus (SLE). However, a positive ANA test may also be seen with non-autoimmune inflammatory diseases, including both acute and chronic infections. When the ANA test is used as an initial screen in patients with non-specific clinical symptoms, such as fever, joint pain, myalgias, fatigue, rash, or anemia, the likelihood of a positive result due to infection will increase, especially in children. This article identifies acute and chronic infectious diseases that are likely to produce a positive ANA result and summarizes recent literature addressing both the causes and consequences of these findings.